The first blind Paranthura species (Crustacea, Isopoda, Paranthuridae) from the 'El Cachucho' Marine Protected Area (Le Danois Bank, southern Bay of Biscay) - Frutos, Inmaculada; Sorbe, Jean Claude; Junoy, Juan (Zootaxa, 2011)
A new paranthurid isopod, Paranthura santiparrai sp. nov. is described from specimens collected in the 'El Cachucho' Marine Protected Area, southern Bay of Biscay. The new species can be distinguished from all the known species of the genus Paranthura by the absence of eyes, from the native NE Atlantic species Paranthura nigropunctata and Paranthura costana by the lack of body pigmentation, antenna 1 and pereopod morphology and from the non-indigenous species Paranthura japonica (recently discovered in the Arcachon Bay) by the pleonites not fused mediodorsally. The genus Paranthura is rediagnosed to accommodate the new taxon and an identification key is provided for European species. Ecological data on the new species are presented.